2020
DOI: 10.1097/prs.0000000000007417
|View full text |Cite
|
Sign up to set email alerts
|

Judging an Expander by Its Cover: A Propensity-Matched Analysis of the Impact of Tissue Expander Surface Texture on First-Stage Breast Reconstruction Outcomes

Abstract: Background: There is increased scrutiny of texturing on implants and a paucity of data looking at texturing on expanders. Because of the difficulty in controlling potential confounders with these comparative studies, the authors performed propensity matching between smooth and textured tissue expander cohorts to provide definitive insight into the impact of expander texture on breast reconstruction outcomes. Methods: A single-surgeon experience with imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
27
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 26 publications
5
27
3
Order By: Relevance
“…15 In contrast with the findings from Wen-Kuan Chiu et al, our study did not find any difference in seroma rates (2% smooth TE, 3.4 textured TE; P = 1) or in infection risk requiring both oral (9.5% smooth TE, 11.3% textured TE; P = 0.6165) and IV (21.8% smooth TE, 20.2% textured TE; P = 0.7986) antibiotics. 15 The complications rates of textured and smooth devices, both short and long term, are better understood in implant devices, with less of an understanding of expander devices due to the paucity of research in this area. Our study is unique in that we retrospectively reviewed 394 patients (147 patients with STEs and 247 with TTEs) who underwent tissue expander placement by multiple surgeons after mastectomy over a 5-year period.…”
Section: Discussioncontrasting
confidence: 99%
“…15 In contrast with the findings from Wen-Kuan Chiu et al, our study did not find any difference in seroma rates (2% smooth TE, 3.4 textured TE; P = 1) or in infection risk requiring both oral (9.5% smooth TE, 11.3% textured TE; P = 0.6165) and IV (21.8% smooth TE, 20.2% textured TE; P = 0.7986) antibiotics. 15 The complications rates of textured and smooth devices, both short and long term, are better understood in implant devices, with less of an understanding of expander devices due to the paucity of research in this area. Our study is unique in that we retrospectively reviewed 394 patients (147 patients with STEs and 247 with TTEs) who underwent tissue expander placement by multiple surgeons after mastectomy over a 5-year period.…”
Section: Discussioncontrasting
confidence: 99%
“…Recently, two studies described complication profiles of TEs specifically, although they did not compare the rate of malpositioning or evaluate time to final reconstruction. 19,20 Both studies reported overall smooth TE complication rates to be lower at 15.6% than textured TE (26.1% and 19.1%) and comparable to rates reported in this study.…”
Section: Discussionsupporting
confidence: 85%
“…Because prevention of malpositioning is a major advantage cited with textured devices, it is important to determine if this is a significant impediment to smooth TE use. Fairchild et al 19 described a smooth expander malposition rate of 2.9% compared with 13.6% reported in this study. Although our rate is notably higher than that reported in the previous study, this could be explained in part in that they included only patients who required surgical correction of the malpositioned pocket.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations